An ISO survey of PAH features in Ultraluminous Infrared Galaxies - Lutz, D; Genzel, R; Rigopoulou, D; Spoon, H; Tran, D; Moorwood, A (1999)
We have obtained ISOPHOT-S low resolution mid-infrared spectra of a sample of 60 Ultraluminous Infrared Galaxies (ULIRGs). We use the strength of the 'PAH' mid-infrared features as a discriminator between starburst and AGN activity, and to probe for evolutionary effects. Observed ratios of PAH features in ULIRGs differ slightly from those in lower luminosity starbursts. We suggest that such PAH ratio changes relate to the conditions in the interstellar medium in these galaxies, and in particular to extinction.